Molas : Dress, Identity, Culture - Marks, Diana, 1954- (Book collections on Project MUSE., 2016)
This book, based on original research, explores the origin of the mola in the early twentieth century, how it became part of the everyday dress of Kuna women, and its role in creating Kuna identity.